Regards de Suissesses et de Camerounaises citadines sur la ménopause : dépasser les dichotomies binaires - Josiane Mbarga (Anthropologie & Santé)
Today, the social construction of menopause is of great interest for many researchers in social sciences. Nevertheless, the way of experiencing this event is still little documented. Following studies debating the underlying logics of the change of menopausal experiences, the aim of this article is to provide a thorough study of the French-speaking and urban Cameroonian’s experiences. Based on interviews with these women, the article shows that, despite the differences that can be observed between their economic, sociocultural and health systems, these women have as many discrepancies as they have similarities in their way of seeing, of living the end of menstruation. Therefore, their menopausal experiences can not be simply classified in two dichotomous groups.